Oriental: a importância do timbre na obra de Pattápio Silva - Daniel Della Savia Silva (2008)
The flutist and composer Pattápio Silva (1880-1907) was one of the Brazilian interpreters that reached larger prominence and projection in the society of his time. In spite of the short career, interrupted by the premature death, when he was 26 years old, Pattápio was considered a great virtuoso of his instrument besides having participated in the historical recordings accomplished in 1902, pioneers in brazil. Influenced by the European flutists' composers, we can highlight in the work of Pattápio Silva his innovative spirit with relation to the exploration of the technique of his instrument, with emphasis in the sound possibilities of the flute. Under these aspects, his work of larger prominence was Oriental op.6 to flute and piano. Through the spectrographic analyses accomplished in the work, we can observe the importance of the variations of tone-color proposed by the author in this piece.